Plug-in hybrid and battery electric vehicles in South Africa: market forecasts - Grant, Andrew (School of Economics, 2016)
This paper uses diffusion modeling to forecast the sales of Plug-in Hybrid and Battery Electric Vehicles (PH/BEVs) in South Africa. First the potential benefits of PH/BEVs in South Africa are scrutinized. The global PH/BEV market is analyzed along with the goals and enticement policies of the countries that are best positioned for a widespread uptake of PH/BEVs. The supply and demand challenges facing the market for PH/BEVs in South Africa are evaluated with a review of current and proposed public policies. The total sales of PH/BEVs in South Africa are then forecast for the medium and long term using an adapted multiple technology generation Bass model with variable parameters for vehicle purchase price and running cost. Two scenarios are examined involving varying oil prices, electricity prices, government support and PH/BEV technological development.